The effect of caffeine on repeat-high-intensity-effort performance in rugby league players - Wellington, B. M.; Leveritt, M. D.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2017)
Context: Repeat-high-intensity efforts (RHIEs) have recently been shown to occur at critical periods of rugby league matches.